Budesonide in the Management of Patients with Crohn's Disease. (1st April 1997) - Thomson, ABR; Sadowski, Daniel; Jenkins, Robert; Wild, Gary
Abstract : Modern medical therapy is increasingly based on evidence. The evidence presented here is that budesonide (Entocort, Astra Pharma) 9 mg/day is superior to placebo and equivalent to systemically active glucocorticosteroids in achieving disease remission in patients with active Crohn's disease, and in prolonging the recurrence time of symptomatic disease. Budesonide causes less disturbance to adrenal function than prednisone or prednisolone and may cause fewer steroid-associated symptoms. Thus, budesonide is the safer, more effective steroid of choice to treat patients with Crohn's disease.